Capsicum leaves under stress: using multi-omics analysis to detect abiotic stress network of secondary metabolism in two species - Reimer, Julia Jessica; Shaaban, Basel; Drummen, Noud; Sanjeev Ambady, Sruthy; Genzel, Franziska; Poschet, Gernot; Wiese-Klinkenberg, Anika; Usadel, Björn; Wormit, Alexandra (Antioxidants, 2022)
The plant kingdom contains an enormous diversity of bioactive compounds which regulate plant growth and defends against biotic and abiotic stress. Some of these compounds, like flavonoids, have properties which are health supporting and relevant for industrial use. Many of these valuable compounds are synthesized in various pepper (Capsicum sp.) tissues. Further, a huge amount of biomass residual remains from pepper production after harvest, which provides an important opportunity to extract these metabolites and optimize the utilization of crops. Moreover, abiotic stresses induce the synthesis of such metabolites as a defense mechanism. Two different Capsicum species were therefore exposed to chilling temperature (24/18 ℃ vs. 18/12 ℃), to salinity (200 mM NaCl), or a combination thereof for 1, 7 and 14 days to investigate the effect of these stresses on the metabolome and transcriptome profiles of their leaves. Both profiles in both species responded to all stresses with an increase over time. All stresses resulted in repression of photosynthesis genes. Stress involving chilling temperature induced secondary metabolism whereas stresses involving salt repressed cell wall modification and solute transport. The metabolome analysis annotated putatively many health stimulating flavonoids (apigetrin, rutin, kaempferol, luteolin and quercetin) in the Capsicum biomass residuals, which were induced in response to salinity, chilling temperature or a combination thereof, and supported by related structural genes of the secondary metabolism in the network analysis.
This article belongs to the special issue "Understanding the Metabolic and Molecular Networking of Antioxidants and ROS Homeostasis in Plants"
Gesehen am 05.09.2022